2019
DOI: 10.1002/ijc.32744
|View full text |Cite
|
Sign up to set email alerts
|

Association of PD‐L1 expression status with the efficacy of PD‐1/PD‐L1 inhibitors and overall survival in solid tumours: A systematic review and meta‐analysis

Abstract: Whether PD-L1-positive patients derive more overall survival benefit from PD-1/PD-L1 inhibitors in the treatment of advanced solid tumours is unclear. We systematically searched the PubMed, Cochrane library and EMBASE databases from January 1, 1966 to March 1, 2019, to identify randomised controlled trials of PD-1/PD-L1 inhibitors (nivolumab, pembrolizumab, atezolizumab, durvalumab and avelumab) that had available hazard ratios (HRs) for death according to PD-L1 status. A random-effects model was used to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…Numerous studies have shown that PD-L1 positive patients can benefit from PD-1 or PD-L1 blockade (18,19). However, recent meta-analyses have confirmed that irrespective of whether PD-L1 is negative or positive, it can benefit from PD-1 or PD-L1 blocking antibodies (20,21). Of the three cases we studied, two were PD-L1 positive and benefited from HMAs combined with PD-1/PD-L1 antibody therapy.…”
Section: Discussionmentioning
confidence: 74%
“…Numerous studies have shown that PD-L1 positive patients can benefit from PD-1 or PD-L1 blockade (18,19). However, recent meta-analyses have confirmed that irrespective of whether PD-L1 is negative or positive, it can benefit from PD-1 or PD-L1 blocking antibodies (20,21). Of the three cases we studied, two were PD-L1 positive and benefited from HMAs combined with PD-1/PD-L1 antibody therapy.…”
Section: Discussionmentioning
confidence: 74%
“…PD-L1 is abundantly expressed on various cancer cells [51,52] and has been extensively summarized in various reviews [13,53]. The discrepancy of some results might be due to inadequate sampling of the tumor and insufficient sensitivity of the detection method/antibody used for immunohistochemistry (IHC).…”
Section: Altered Pd-l1 Expression In Tumorsmentioning
confidence: 99%
“…In a recent meta-analysis (37,38), evidence showed that PD-1/PD-L1 inhibitors significantly improve OS in patients with either PD-L1 positivity or PD-L1 negativity compared with controls (37,38). However, in these meta-analyses (37,38), patients with SCLC were not included; therefore, further studies should be conducted to investigate the impact of PD-L1 expression on the prognosis of patients with SCLC receiving ICIs. Although we performed this meta-analysis based on the PRISMA guidelines, several limitations must be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the current meta-analysis, all included studies did not enroll patients receiving ICIs; therefore, whether PD-L1 expression is associated with the efficacy of ICIs and OS in patients with SCLC remains unclear. In a recent meta-analysis ( 37 , 38 ), evidence showed that PD-1/PD-L1 inhibitors significantly improve OS in patients with either PD-L1 positivity or PD-L1 negativity compared with controls ( 37 , 38 ). However, in these meta-analyses ( 37 , 38 ), patients with SCLC were not included; therefore, further studies should be conducted to investigate the impact of PD-L1 expression on the prognosis of patients with SCLC receiving ICIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation